(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Information technology has revolutionized almost every aspect of life, including governance, by fostering good governance, accountability, and transparency through e-governance, which has substantially changed how the government deals with the public and private sectors. In the present information technology era, the extent to which e-governance is implemented in a nation is a key indicator of its level of development. E-governance, with its attributes of accountability, openness, and public participation, serves as a vital platform to improve the standard of timely state service delivery to the citizens. Thus, in order to assess the potential application of e-governance in the Indian context among the under-30 age-group citizens, this paper has attempted to determine the level of awareness and usage. The primary goal of the study is to determine the degree of e-governance service adoption and knowledge, as well as the reasons behind non-use of these services and the effects of the lockdown during the Covid-19 pandemic on these factors. The study aims to ascertain the degree of gender disparity and occupational distribution in the awareness and usage of e-governance services among the individuals who have been selected from the aforementioned age groups for the study